(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Tunnels are one of the prominent structures used for transportation. The current researchreviews the existing work on tunnel design and analysis. These studies are based on use of bothexperimental and numerical techniques. The fundamental principles underlying tunnel design,geotechnical considerations are presented. The advantages, limitations of different techniques,processes are presented. Various case studies are presented to illustrate the application of theseapproaches in different geological and geotechnical contexts.